Mathematical creative thinking ability of 7th grade student observed from self-confidence in learning RTTW with open ended approach - Prasetyowati, Nugraheni; Dwijanto, Dwijanto (Department of Mathematics, Universitas Negeri Semarang, 2019)
The purpose of this research is to test students' creative thinking abilities in RTTW learning with open ended approach to achieve individual and classical learning completeness, to test the mathematical creative thinking abilities of students taught in RTTW learning with open ended approach better than Discovery Learning, to describe thinking skills students' mathematical creativity observed from self-confidence in RTTW learning with open ended approach. The method used is mixed method. Quantitative methods are used to determine students' mathematical creative thinking abilities using tests, while the qualitative method used documentation and interviews. The study population was students of Junior High School Grade 7th, with class VII F as the experimental class and VII E as the control class. The research subjects were 6 subjects chosen based on the self-confidence category of class VII F. The results showed that (1) the results of RTTW learning with open ended approach to completing individual learning completeness, (2) the results of the RTTW learning had an open ended approach to achieving classical learning completeness, (3 ) the mathematical creative thinking abilities of students in RTTW learning with open ended approach better than Discovery Learning, (4) subjects of the upper self-confidence group are able to meet 4 indicators, the middle group is able to meet 2 indicators, the lower group is able to meet 1 indicator.